ANALISIS PEMANFAATAN SUMBER BELAJAR DAN PENGARUH NYA TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - alikhsan, Wahyu fadli; Gimin, Gimin; Hendripides, Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : The purpose of this study was to determine the use of learning resources and their effects on learning outcomes in FKIP Economics Education students at Riau University. The population in this study were students of the University of Riau's economic education and the sample to be studied was 122 students. In this study using a sample technique Proposional random sampling sample randomly determined all populations have the opportunity to be sampled. Data collection using questionnaires. Data analysis uses quantitative descriptive analysis. The purpose of this study was to determine the use of learning resources used to affect learning outcomes. Based on the results of the study showed that the use of the internet is very often used as a learning source that is equal to 60%, followed by textbooks with frequent categories of 68% and other reading sources with rarely used categories at 60%.Keywords: internet usage, textbooks and other reading, learning outcomes